YouTube Media on Arabic Language Acquisition Early Childhood 4 Years Old - Misbahuddin; Setiyawan, Agung (Asalibuna, 2023)
The purpose of this study is to describe the second language acquisition of a child case study conducted through YouTube social media. Children who have not mastered the language can use YouTube media. This research uses qualitative and descriptive methodology. This study concentrates on basic vocabulary, namely nouns or animal names, as well as basic numeralia, namely numbers 1 to 10. The results of this study show that YouTube has a relevant impact on children's second language acquisition. Nonetheless, YouTube media does not absolutely depict the role of humans in language education and learning. The implications of this research can lead to the development of more innovative and effective learning methods to support Arabic language acquisition in early childhood. The utilization of YouTube media can be an inspiration to develop learning strategies that are more interesting and in accordance with the characteristics of child development